First, rewrite the equation so that y is a function of x :
![x^4 = y^6 \implies \left(x^4\right)^(1/6) = \left(y^6\right)^(1/6) \implies x^(4/6) = y^(6/6) \implies y = x^(2/3)](https://img.qammunity.org/2022/formulas/mathematics/college/jnv7ooper7ifu5vwyzynzo67y03rfaf0az.png)
(If you were to plot the actual curve, you would have both
and
, but one curve is a reflection of the other, so the arc length for 1 ≤ x ≤ 8 would be the same on both curves. It doesn't matter which "half-curve" you choose to work with.)
The arc length is then given by the definite integral,
![\displaystyle \int_1^8 \sqrt{1 + \left((\mathrm dy)/(\mathrm dx)\right)^2}\,\mathrm dx](https://img.qammunity.org/2022/formulas/mathematics/college/fkeac1labpqogeescsmqgkwywyi2lvep6i.png)
We have
![y = x^(2/3) \implies (\mathrm dy)/(\mathrm dx) = \frac23x^(-1/3) \implies \left((\mathrm dy)/(\mathrm dx)\right)^2 = \frac49x^(-2/3)](https://img.qammunity.org/2022/formulas/mathematics/college/wloxwujm5onm74d445kqtawuprgv3p9jcs.png)
Then in the integral,
![\displaystyle \int_1^8 \sqrt{1 + \frac49x^(-2/3)}\,\mathrm dx = \int_1^8 \sqrt{\frac49x^(-2/3)}\sqrt{\frac94x^(2/3)+1}\,\mathrm dx = \int_1^8 \frac23x^(-1/3) \sqrt{\frac94x^(2/3)+1}\,\mathrm dx](https://img.qammunity.org/2022/formulas/mathematics/college/a68jleymexlewpfj47s5wldmvtolloukx1.png)
Substitute
![u = \frac94x^(2/3)+1 \text{ and } \mathrm du = (18)/(12)x^(-1/3)\,\mathrm dx = \frac32x^(-1/3)\,\mathrm dx](https://img.qammunity.org/2022/formulas/mathematics/college/yufgyaqbpvy79gn43zp0h821mjf0ukihsj.png)
This transforms the integral to
![\displaystyle \frac49 \int_(13/4)^(10) √(u)\,\mathrm du](https://img.qammunity.org/2022/formulas/mathematics/college/ec6jp0olkioi8z4hb34huy7b91yo8uv0mn.png)
and computing it is trivial:
![\displaystyle \frac49 \int_(13/4)^(10) u^(1/2) \,\mathrm du = \frac49\cdot\frac23 u^(3/2)\bigg|_(13/4)^(10) = \frac8{27} \left(10^(3/2) - \left(\frac{13}4\right)^(3/2)\right)](https://img.qammunity.org/2022/formulas/mathematics/college/6psj8qr72kwyja4alqh1az6wzdpmtaaxnh.png)
We can simplify this further to
![\displaystyle \frac8{27} \left(10√(10) - \frac{13√(13)}8\right) = \boxed{(80√(10)-13√(13))/(27)}](https://img.qammunity.org/2022/formulas/mathematics/college/fpyq080bchesn0em4eopzfd52ljjtqc1z4.png)